Study of Cerebrospinal Fluid (CSF) and Clinical and Electrophysiological Features of Hospitalized Patients with Gullain-Barre´ Syndrome - Huda, Md Nazmul; Khan, Mohammed Momenuzzaman; Azam, Bakhtiar; Uddin, Md Jalal (Journal of Enam Medical College, 2015)
Background: Since the elimination of poliomyelitis from most part of the world Gullain-Barre' Syndrome (GBS) has been the leading cause of acute flaccid paralysis which leads to substantial morbidity and mortality. Though GBS has received a lot of attention in developed countries, there is a paucity of reports on the GBS from the developing world including Bangladesh. Objective: The objective of the study was to correlate clinical, cerebrospinal fluid (CSF) and electrophysiological findings of hospitalized Gullain-Barre´ syndrome patients for early diagnosis and appropriate management. Materials and Methods: A total of 47 clinically diagnosed GBS patients admitted in Neurology, Medicine and Pediatrics departments of Dhaka Medical College Hospital (DMCH) were included in this quasi-experimental study. Biochemical, cytological and bacteriological studies of CSF of these patients were done. Electrophysiological studies of all subjects were done and values were compared with upper and lower limits of normal. Results: In this study, antecedent event were present in 55.30% cases and upper respiratory infection (23.40%) and gastroenteritis (21.30%) were the commonest antecedent disorders. All the study patients had numbness or paresthesia and limb weakness, and muscle pain was in 44.7% cases, facial weakness in 36.2% cases, ophthalmoplegia or ptosis in 6.4% and bulbar involvement was in 6.4% cases. Most of the patients (95.7%) had deep tendon hypo/areflexia followed by respiratory distress (21.3%), and ataxia (19.1%). Majority of the study patients (57.4%) required one week time to develop maximum deficit. Maximum subjects (70.2%) had motor type GBS followed by sensorimotor type (21.3%), Miller-Fisher type (6.4%) and sensory type (2.1%). Eighty three percent of the study patients had CSF protein concentration >45 mg/dL with mean ± SD of 71.32 ± 20.20 mg/dL (37112 mg/dL). The cell count in CSF was <5 per mm3 in 95.7% of the study patients with mean ±SD cell count of 3.2 ± 1.80/mm3 (215 cells per mm3). The mean ± SD time to perform EMG was 9.4 ± 3.6 days with a range from 517 days and the mean ± SD disability grade at that time to EMG was 3.6 ± 0.9 with a range from 25. Regarding the electrodiagnostic types, the commonest pattern (40.40%) was found AIDP, AMAN was 29.80%, AMSAN 19.15% and mixed pattern was in 10.65% of the patients. Conclusion: This study reveals that clinical, CSF and electrophysiological findings accurately diagnose the GBS patients along with typing of GBS. J Enam Med Col 2015; 5(3): 145-150